Structural Load Determination : 2024 IBC and ASCE/SEI 7-22 - Fanella, David A. (McGraw-Hill's AccessEngineeringLibrary., 2024)
This practical guide shows, step by step, how to interpret and apply the load provisions in the 2024 IBC? and ASCE/SEI 7-22. The book contains fundamental information that is needed to design buildings to withstand gravity and environmental loads. Many new figures, flow charts, design aids, and example problems are given-all worked out in both inch-pound and metric units. Written by an experienced structural engineer and co-branded with the ICC, Structural Load Determination: 2024 IBC and ASCE/SEI 7-22 is a useful resource for practicing engineers, professors, students, building officials, and plan checkers"-- Provided by publisher.